India Development Update, May 2017 : Unlocking Women’s Potential - World Bank (World Bank, New Delhi, 2017)
India has among the lowest female labor force participation rates (LFPRs) in the world. In particular, low female LFPR is a drag on Gross Domestic Product (GDP) growth and an obstacle towards reaching a higher growth path. Women are also an untapped source of managerial and entrepreneurial skills. By excluding women, the pool of such talent becomes shallower and growth suffers. If the overall lack of jobs, especially regular salaried jobs, plays a large role in India’s female LFPR, only a combination of gender-targeted and broader policies towards formal job creation can sustainably raise female LFPR and accelerate India’s GDP growth and broader social development. Policies that promote job creation in women-friendly sectors such as apparel, or that help fast-growing modern service sectors absorb more educated women workers would be particularly helpful.